A comprehensive study on morphological and rheological behavior of poly(ethylene terephthalate) and poly(ethylene‐2, 6‐naphthalene) nanocomposite blends in presence of graphene. (4th January 2016) - Ghadami, Azam; Ehsani, Morteza; Khonakdar, Hossein Ali
Abstract : This study is concerned with morphological and rheological behavior of several systems based on poly(ethylene terephthalate) (PET), poly(ethylene‐2, 6‐naphthalene) (PEN), PET/PEN blend, and their graphene‐filled nanocomposites. The composites were prepared by using a melt‐mixing method and analyzed by scanning electron microscopy and transmission electron microscopy techniques. It was observed that the graphene nanosheets were almost distributed uniformly, especially in the blend matrix. The applied mixing method was easily able to disperse nanographene as well as the initial aggregates in polyester and the blend system. By performing rheological examinations, the elastic modulus, viscosity, loss curve, and relaxation spectra of the samples were fully investigated. The presence of graphene had different effects on rheological properties such as viscosity and modulus in two polyester matrices and their blends. In all nanocomposite samples, with the addition of 1 wt% graphene, the elasticity level dropped relative to that of neat polyesters. In PEN nanocomposites, the tan δ peak appeared with the addition of graphene. However, in PET nanocomposites, the tan δ peak developed at higher frequency, with a low percentage of graphene nanosheets, and became narrower at greater quantity, compared with neat PET. By addition of nanographene into the blend, the damping factor increased. The relaxation spectra, H (τ), helped to better understand the viscoelastic properties in the long‐time region, and it was demonstrated that the graphene sheets retarded the relaxation process of polyesters in the molten state. The results of relaxation spectra and storage modulus agreed with each other, and similar trends were observed in all the samples under examination . J. VINYL ADDIT. TECHNOL., 23:E160–E169, 2017. © 2016 Society of Plastics Engineers